Multi-disciplinary reconstruction of debris flow events and dynamics in the Northern Apennines, Italy: A multi-scale approach linking ground evidence with climatic triggers - Muhammad Ahsan Rashid; Alessandro Chelli; Emma Petrella; Sara Pescio; Jacopo Melada; Veronica Manara; Bruno Arcuri; Maurizio Maugeri; Michele Brunetti; Luca Trombino; Anna Masseroli; Giovanni Leonelli (CATENA, 2026)

ITV-net: a dataset of intraspecific leaf traits data across major Italian habitats - Stefano Chelli; Alessandro Bricca; Francesco Petruzzellis; Enrico Tordoni; Giacomo Calvia; Alicia T.R Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; et al. (Plant Biosystems, 2025)

How effective are different protection strategies in promoting the plant diversity of temperate forests in national parks? - Zhengxue Zhu; Stefano Chelli; James L. Tsakalos; Alessandro Bricca; Roberto Canullo; Marco Cervellini; Riccardo Pennesi; Luciano L.M. De Benedictis; Vanessa Cesaroni; Alessandro Bottacci; Giandiego Campetella (Forest Ecology and Management, 2025)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Multiple drivers of functional diversity in temperate forest understories: Climate, soil, and forest structure effects - Stefano Chelli; Alessandro Bricca; James L. Tsakalos; Anna Andreetta; Gianmaria Bonari; Giandiego Campetella; Stefano Carnicelli; Marco Cervellini; Nicola Puletti; Camilla Wellstein; Roberto Canullo (Science of The Total Environment, 2024)

Spatial distribution patterns of dated landslide events in the Northern Apennines in response to Holocene regional climatic changes - Giovanni Leonelli; Alessandro Chelli (CATENA, 2024)

Intraspecific variability of leaf form and function across habitat types - Giacomo Puglielli; Alessandro Bricca; Stefano Chelli; Francesco Petruzzellis; Alicia T. R. Acosta; Giovanni Bacaro; Eleonora Beccari; Liliana Bernardo; Gianmaria Bonari; Rossano Bolpagni; Francesco Boscutti; Giacomo Calvia; et al. (Ecology Letters, 2024)
Trait‐based ecology has already revealed main independent axes of trait variation defining trait spaces that summarize plant adaptive strategies, but often ignoring intraspecific trait variability (ITV). By using empirical ITV‐level data for two independent dimensions of leaf form and function and 167 species across five habitat types (coastal dunes, forests, grasslands, heathlands, wetlands) in the Italian peninsula, we found that ITV: (i) rotated the axes of trait variation that define the trait space; (ii) increased the variance explained by these axes and (iii) affected the functional structure of the target trait space. However, the magnitude of these effects was rather small and depended on the trait and habitat type. Our results reinforce the idea that ITV is context‐dependent, calling for careful extrapolations of ITV patterns across traits and spatial scales. Importantly, our study provides a framework that can be used to start integrating ITV into trait space analyses.

Training on the topic of landslides and slope stability in Rwanda: a Summer School in the framework of the Erasmus + EnRHEd project - Roberto Valentino; Alessandro Chelli; Emma Petrella (Landslides, 2023)

Species trait syndrome drives the leaves’ functional variations of dominant grasses to modifications in summer water supply - Federico Maria Tardella; Alessandro Bricca; Stefano Chelli; Giandiego Campetella; Roberto Canullo; Maurizio Cutini; Irina G. Goia; Nicola Postiglione; Andrea Catorci (Plant Ecology, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Plant–environment interactions through a functional traits perspective: a review of Italian studies - Stefano Chelli; Michela Marignani; Elena Barni; Alessandro Petraglia; Giacomo Puglielli; Camilla Wellstein; Alicia T. R. Acosta; Rossano Bolpagni; Luca Bragazza; Giandiego Campetella; Alessandro Chiarucci; Luisa Conti; et al. (Plant Biosystems, 2019)

Groundwater characterization from an ecological and human perspective: an interdisciplinary approach in the Functional Urban Area of Parma, Italy - Andrea Zanini; Emma Petrella; Anna Maria Sanangelantoni; Letizia Angelo; Beatrice Ventosi; Luca Viani; Pietro Rizzo; Sara Remelli; Marco Bartoli; Rossano Bolpagni; Alessandro Chelli; Alessandra Feo; et al. (Rendiconti Lincei. Scienze Fisiche e Naturali, 2019)

Litter decomposition: effects of temperature driven by soil moisture and vegetation type - Alessandro Petraglia; Cecilia Cacciatori; Stefano Chelli; Giuseppe Fenu; Giulia Calderisi; Domenico Gargano; Thomas Abeli; Simone Orsenigo; Michele Carbognani (Plant and Soil, 2019)

Landslides types controlled by tectonics-induced evolution of valley slopes (Northern Apennines, Italy) - Mirko Carlini; Alessandro Chelli; Roberto Francese; Serena Giacomelli; Massimo Giorgi; Andrea Quagliarini; Andrea Carpena; Claudio Tellini (Landslides, 2018)

Quantitative Estimates of Bio-Remodeling on Coastal Rock Surfaces - Marta Pappalardo; Markus Buehler; Alessandro Chelli; Luca Cironi; Federica Pannacciulli; Zhao Qin (Journal of Marine Science and Engineering, 2016)
Remodeling of rocky coasts and erosion rates have been widely studied in past years, but not all the involved processes acting over rocks surface have been quantitatively evaluated yet. The first goal of this paper is to revise the different methodologies employed in the quantification of the effect of biotic agents on rocks exposed to coastal morphologic agents, comparing their efficiency. Secondly, we focus on geological methods to assess and quantify bio-remodeling, presenting some case studies in an area of the Mediterranean Sea in which different geological methods, inspired from the revised literature, have been tested in order to provide a quantitative assessment of the effects some biological covers exert over rocky platforms in tidal and supra-tidal environments. In particular, different experimental designs based on Schmidt hammer test results have been applied in order to estimate rock hardness related to different orders of littoral platforms and the bio-erosive/bio-protective role of Chthamalus ssp. and Verrucariaadriatica. All data collected have been analyzed using statistical tests to evaluate the significance of the measures and methodologies. The effectiveness of this approach is analyzed, and its limits are highlighted. In order to overcome the latter, a strategy combining geological and experimental–computational approaches is proposed, potentially capable of revealing novel clues on bio-erosion dynamics. An experimental-computational proposal, to assess the indirect effects of the biofilm coverage of rocky shores, is presented in this paper, focusing on the shear forces exerted during hydration-dehydration cycles. The results of computational modeling can be compared to experimental evidence, from nanoscopic to macroscopic scales.

Field investigations and monitoring as tools for modelling the Rossena castle landslide (Northern Appennines, Italy) - Alessandro Chelli; Giuseppe Mandrone; Giovanni Truffelli (Landslides, 2006)